Analisis Kebutuhan Modul Pembelajaran Kearifan Lokal Sedekah Bumi untuk Meningkatkan Ekoliterasi pada Pembelajaran Bahasa Indonesia - Aprilia Rizki Arifah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Environmental problems are of global concern. Integration of ecology-based local wisdom in education needs to be done to increase ecoliteracy. This research aims to describe the need for a teaching module for the earth alms ceremony to increase ecoliteracy in Indonesian language learning in high school. The research method used is a qualitative method. Data collection techniques used questionnaires and interviews. Based on the results of the analysis, it was found that students need teaching modules based on local ecological wisdom in learning Indonesian. Students already have awareness of the importance of increasing ecoliteracy in learning. Most students have an interest and curiosity in studying the Indonesian language teaching module which contains material about the earth alms ceremony in Banyumas. This need is also increasingly important because of the limited teaching modules available, students' lack of understanding of local wisdom in their area, and the lack of sources for learning local wisdom.